Avaliação de práticas de produção mais limpa e sua relação com o desempenho organizacional: survey no setor têxtil brasileiro - Silva, Paulo Cesar da (2016)
The textile industry is known as one of the main polluting industries to the environment due to its complex sectored operations diversified in production chain processes and types of pollutants. The growing concern about negative environmental impacts and business sustainability, has led companies to adopt environmental tools and strategies, such as Cleaner Production. Analogous to this some initiatives of implementing Cleaner Production in the textile industry have been made in spinning, weaving, finishing, printing and apparel sectors, focusing on reducing waste, pollution, emissions and process modifications according to literature. This research objective is to assess whether the implementation of Cleaner Production by Brazilian textile companies has a positive or negative effect in the economic, environmental and operational performances. Specifically aims to identify which Cleaner Production practices are most or least used by Brazilian textile industry. The method adopted to reach this objective will be a survey in companies of Brazilian textile sector. The results demonstrated overall positive impact of CP practices for all three performances in the following relevance order: operational, environmental and economic performance. The proposed model was able to identify the most relevant CP practices, which have higher coefficient values for the constructs related to the operational and environmental performance. The less relevant practices, contributed to lower coefficient value for the construct of economic performance due to the fact that investments in clean technologies for energy efficiency, selection of suppliers and improvement of working conditions require high investments with a long time return. The main contribution of this research consist in developing a relation model of constructs, CP practices, operational, environmental and economic performance, that can measure the contributions of the respective constructs for companies inside and outside the textile sector.